What are we missing? Three cases of severe COVID-19 pneumonia with negative testing. (October 2020) - Siddiqui, Aisha; Singh, Sukhdev; Khan, Zohaib; Foster, Allison; Atere, Muhammed; Nfonoyim, Jay M
The COVID-19 pandemic has drastically affected health care systems globally. Reverse transcriptase-polymerase chain reaction is currently the preferred method of detecting COVID-19; however, sensitivity of this test remains questionable. Incidental transmission and potential harm to infected individuals are some consequences of the failure to identify high-risk patients. We report three cases of symptomatic patients that required intensive care management with labs and imaging consistent with COVID-19 with initial false-negative reverse transcriptase-polymerase chain reaction testing. Improper sampling, viral load, and manufacturer variances of tests all contribute to reduced sensitivity. A clinical diagnosis should supplant such cases.